Ecology In the Modern World - Kholova Shokhista Abdurashidovna (Zien Journals, 2022)
This article is about ecology in the modern world. Today industrial ecology encompasses a very wide range of problems, moreover, problems of very different and no longer biological ones. Here it is more appropriate to talk about a number of environmental engineering disciplines: the ecology of the mining industry, the ecology of energy, the ecology of chemical industries, etc
Keywords: ecology; process; Agricultural activity; human activity